A rhetorical approach to the genre of the abstract within the field of Food Science and Technology - María Milagros del Saz Rubio (Pragmalingüística, 2019)
In this paper I have outlined the rhetorical structure of 50 abstracts from the field of Food Science and Technology and have assessed how metadiscoursal features are used across its different moves. 25 abstracts were authored by researchers with English as their L1, and other 25 were written by Spanish researchers. In general terms, 54% of the abstracts deploy the moves traditionally associated with the IRMD and CARS structure, whereas 46% of the abstracts exclusively follow the IMRD structure and, hence, do not use topic contextualization or gap signalling. English researchers tend to write more complex abstracts with regard to move and steps deployment. Interpersonal features occur with a normalized frequency of 29.2 per 1000 words, especially in moves 5 (56% of the features), 1 (16%), 6 (14%) and 3 (10%). English researchers tend to use metadiscoursal features with a slightly higher frequency (59%) than the Spanish group (41%).